A study on the protective effects of calcium channel blockers against anoxic brain damage - Sunil, Gurtu; S.B, Acharya; H. A., Nadiger; Mohd, Shakil Siddiqui (1997)
Introduction It is now widely accepted that a rapid neuronal influx of Ca2+ following cerebral ischaemia! hypoxia is intimately connected with the cascade of events- including activation of enzymes which give rise to the production of reactive oxygen species and nitric oxide, thereby leading to free-radical induced damage -which reseult in neuronal injury and death. It is also known that a burst of free radical generation I occurs during re-oxygenation of the tissues following a period,ofischaernialhypoxia as also a prolonged purturbation of the membrane functions continues after the perfusion/oxygenation has been restored, which leads to continued accumulnnon of calcium intracellularly ; resulting ultimately in delayed damage and death of the neurone. Estimation of lipid peroxidation products proviqes a reliable estimate of free radical induced damage to tissues, and has been widely used for this purpose.